Изучение научного функционального стиля во второй половине ХХ- в. - КОЖИНА, МАРГАРИТА Н.; КОТЮРОВА, МАРИЯ П. (Stylistyka, 2021)
The article disusses the main directions in investigating the scientific style of the Russian language in the second half of the 20th с. and the results obtained.